The Correlation between Diction Mastery and Carefulness with Students' Writing Ability - Mira Sari; Wayan Satria Jaya; Supriyono Supriyono; Nani Angraini (IJLHE: International Journal of Language, Humanities, and Education, 2019)
This study aims to determine the correlation between diction and punctuation mastery with the student's writing ability. The method used in this study is the correlational method, which is to find out and describe the relationship between diction mastery and persuasive writing ability, the relationship between punctuation mastery and persuasive writing ability, and the relationship between diction and punctuation mastery and students' writing ability. The results of this study are 1) There is a positive and significant relationship between mastery of diction and t students' writing ability with the correlation coefficient = 0.483, while the contribution given by the variable mastery of diction to students' writing ability is 23,329% and the remaining 76,671% is determined by other factors/variables; 2) There is a positive and significant relationship between the mastery of punctuation and the students' writing ability with a correlation coefficient of r = 0.829, while the contribution given by the variable mastery of punctuation to students' writing ability is 68.724%, then the remaining 31.276% is determined by other factors/variables; 3) There is a positive and significant relationship between mastery of diction and punctuation with students' writing ability with a correlation coefficient of R = 0.848, while the contribution given is 71.91%, then the remaining 28.09% is determined by other variables/factors. These results show that the variable mastery of diction and punctuation has strongly influenced the students' writing ability.